Perlindungan Hukum Bagi Konsumen Nasabah BANK Pemegang Kartu Kredit yang Dibebankan Biaya Tambahan (Surcharge) oleh Merchant dalam Transaksi Pembayaran - Ni Putu Dyah Ayu Karina Prabandari; I Nyoman Putu Budiartha; Anak Agung Sagung Laksmi Dewi (Warmadewa Press, 2022)
The development of technology and information makes credit cards in demand by the public. However, consumer protection has not been able to fully guarantee legal protection for consumers, especially for bank customers who hold credit cards. The purposes of this study are to reveal the legal protection arrangements for consumer bank customers who are credit card holders who are charged an additional fee (surcharge) by merchants in payment transactions as well as sanctions against merchants who charge additional fees (surcharge) for consumer bank customers who are credit card holders in payment transactions. This research method is a normative research with a statutory and conceptual approach. The technique of collecting legal materials is done by using library techniques. The sources of legal materials used are primary, secondary, and tertiary legal sources. After the data is collected, then the legal materials are analyzed qualitatively. The results of the study reveal that legal protection for credit card holders is categorized into 3 (three) stages, namely before the transaction, during the transaction, and after the transaction. It is hoped that the government will coordinate with the competent authorities. Bank Indonesia and the Financial Services Authority (OJK) should be able to make stricter regulations regarding the protection of credit card holders